Analisis Praktik Kewirausahaan Mahasiswa Melalui Inovasi Produk Teh - Anwar SA (Journal of New Trends in Sciences, 2025)
Entrepreneurship has long been recognized as a driving force for a country's socioeconomic growth, becoming increasingly important in facing the challenges of globalization, which demand creativity and innovation. Fierce competition demands that students, as the younger generation, possess greater competencies to compete in the workforce. Student involvement in entrepreneurship can foster the development of an innovation ecosystem on campus, which in turn can improve the quality of education and research. This scientific article aims to analyze students' entrepreneurial practices in creating innovative tea products during their studies, with a focus on identifying factors influencing success and the challenges faced. Students' tea product innovations not only add value to the industry but also provide valuable experience in developing entrepreneurial skills. The research method used was a qualitative approach, interviewing students who own tea product businesses. The results show that students who are entrepreneurs in tea product businesses are highly motivated, highly creative, and have good adaptability. However, they also face various challenges, such as limited capital, lack of experience, and intense competition.